Effect of Cyclone Diffuser Swirl throughout 30 mm On Liquid Jet Gas Pump (Application on Frying Pineapple Chips) - Eswanto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2016)
Pineapple is a plant that is widely available in Indonesia and fruit favored by the public. Some areas in North Sumatra as langkat, Binjai, Berastagi, Siborong-borong many supply pineapples to the city field, so if at the time of pineapple fruit season arrives, the city became a flood pineapple field and consequently if the fruit is not sold will be rotten. Seeing this need to utilize technology in order not rotten pineapple and wasted, therefore there is need to do an experiment to make a pineapple into chips with technology liguid jet gas pump (LJGP) which method a way with a vacuum system. From the problems necessary to study to get the best vacuum LJGP tool is one of them by adding a Cyclone vortex diffuser models. The purpose of this study is to obtain the best vacuum as well as the efficiency of LJGP that can be used in frying applications pineapple crisps vacuum method along the vortex diffuser 30 mm. The research method with experiments involving fluid water and air, by adding a Cyclone vortex Diffuser models in LJGP tool as long 30 mm. The observed data is the primary flow rate (primary flow / motive flow) is 0.32 L / s, up to 0.44 L / s and discharge secondary flow (secondary flow) ranged from 0.04 L / s to 0.2 L / s. As for the water to circulate fluid LJGP, used types of centrifugal pumps with a capacity of 340 L / min. From the research that has been done shows that the more points cyclone vortex diffuser, the secondary pressure will increase. The maximum secondary pressure in the cyclone vortex diffuser length 30 mm which is 150 215 kPa, with secondary pressure maximum of 12 GPM is present in 1,367 kPa. This condition is informed that the use of models in the vortex of Cyclone Diffuser LJGP tool is in need to improve the vacuum system for LJGP.